Caries preventing efficacy of new Isomalt-containing mouthrinse formulations: a microbial study - Bennett T. Amaechi; Parveez Ahamed AbdulAzees; Sahar Mohseni; Minh N. Luong; Chun-Yen Lin; Maria Camila Restrepo-Ceron; Yuko Kataoka; Temitope O. Omosebi; Kannan Kanthaiah (Nature Publishing Group, 2024)
Abstract Objectives The effectiveness of an Isomalt-containing mouthrinse to prevent caries development was investigated. Methods Human enamel blocks were randomly assigned to five groups (n = 30/group): De-ionized distilled water (DDW), and mouthrinse containing either (IFC) 1% Isomalt, 225 ppm fluoride, and 0.05% cetylpyridinium chloride (CPC), (IF) 1% Isomalt and 225ppm fluoride, (FC) 225 ppm fluoride and 0.05% CPC or (F) 225 ppm fluoride. During 7-day demineralization in a Microbial Caries Model, mouthrinses were applied once daily for 1 min. Demineralization was assessed using Surface Microhardness testing for percentage change in SMH (%ΔSMH) and Transverse Microradiography for mineral loss (ΔZ). Data analysis (α = 0.05) used paired t-test (Intra-group comparison using SMH) and ANOVA/Tukey's for inter-group comparisons (%ΔSMH and ΔZ). Results With SMH, relative to sound enamel baseline, demineralization was significant (P < 0.001) in all groups, except in IFC. Intergroup comparison with %ΔSMH showed significantly (p < 0.001) greater demineralization in DDW compared to other groups, and in IF, FC, and F compared to IFC (P < 0.001). With ΔZ, relative to DDW, all groups significantly (p < 0.0001) inhibited demineralization at varying percentages. Conclusions Mouthrinse containing Isomalt, fluoride, and CPC inhibited demineralization amidst cariogenic biofilm; thus, highlighting its potential as a more effective caries control tool than mouthrinse with only fluoride.